Der Einfluss von Migräne auf den Bedarf von Lokalanästhetika - Valcárcel, C. Yañez; Wolowski, A.; Ehmke, B.; Evers, S. (Nervenheilkunde, 2014)
Background: In experimental settings, migraine patients show a reduced pain threshold in the trigeminal region. However, only little is known about the relevance of this phenomenon for other pain conditions. We evaluated pain perception of migraine patients during dental treatment by counting the amount of local anaesthetics. Methods: We enrolled 30 migraine patients and 133 control patients without migraine who underwent a major surgical dental procedure. We evaluated the amount of local anaesthetics (in ml of lidocaine equivalents) as demanded by the patients during this procedure. Further, patients received a diary to record their pain and the amount of analgesics during the following seven days. Results: The need for local anaesthetics was significantly higher in the group of control patients than in the migraine patients. The amount of totally applied local anaesthetics in ml was significantly lower in migraine patients. Migraine patients showed significantly higher pain levels in the seven days after the procedure. Discussion: We could show that the differences in trigeminal pain perception between migraine and non-migraine patients which have been shown in different experimental settings can also be shown in routine clinical situations. These differences are even relevant e.g. for the amount of anaesthetics and for the level of pain induced by such routine procedures.
Keywords: Migraine; local anaesthetics; dental procedure; pain perception